JENIS-JENIS DAN PEMANFAATAN TANAMAN OBAT DI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI SEBAGAI RANCANGAN BUKU SAKU PEMBELAJARAN BIOLOGI SMA - Happy Kurniawan; Yuslim Fauziah; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the types of medicinal plants by inventorying and identifying medicinal plants that are used as traditional medicine by the people of Benai District, Kuantan Singingi Regency. This research is a qualitative research. Data on the types of medicinal plants in Benai District, Kuantan Singingi Regency were obtained through interviews and direct observation at the research location. The data collection instrument was in the form of an interview guide sheet. This research was conducted in Benai District, Kuantan Singingi Regency, Riau for two weeks in early October. Sampling was carried out in 3 countries, namely; The horrors of Benai, Siberakun, Simandolak. The results of the research regarding the inventory of traditional medicinal plant species in Benai District, Kuantan Singingi Regency found as many as 43 types of medicinal plants that were successfully identified which belonged to 27 plant families and will later be used to design a pocket book that can be used as a Biology learning resource.Keywords: Benai District, Biology Learning, Medicinal Plants